Process simulation and energy consumption for CO2 capture with different flowsheets. (2017) - Xue, Boyang; Yu, Yanmei; Chen, Jian
In this work, a systematic simulation study of post-combustion CO2 capture process is presented. Including six individual process modifications and six combinations of process modifications, 13 different process configurations are simulated using aqueous monoethanolamine (MEA) and diethanolamine (DEA) solutions. Process modifications presented a good performance with respect to the reduction of energy consumption. It is carried out with 3.45% to 13.45% of reduction for MEA and 2.36% to 14.10% for DEA. Furthermore, a detailed analysis is presented to study the effect of three significant parameters in capture process, i.e., CO2 loading of lean amine solvent, pinch of heat exchanger and stripper pressure. This work presents the influence of the combination of solvent and process, as well as the combination of different processes on energy consumption, which are essential in post-combustion process design to make optimisation strategy.